The desire for truth: Plato’s proposal and the biblical context in the light of René Girard’s mimetic theory and the scapegoat mechanism - Gotchold, Agnieszka (Filozofia Chrześcijańska, 2019)
The paper discusses the issue of the desire for truth in Plato’s Republic, Book VII, and the Old and New Testaments with regard to Girard’s theory of mimetic desire, the scapegoat mechanism and the founding murder. Both Plato and the Bible describe outstanding individuals – Anax, Moses and Jesus – who attain truth. This causes communal envy, leading to the outbreaks of mimetic violence. However, neither Plato nor the Old Testament allow the founding murder to happen. Consequently, they depict communities which deal with strict laws and suppressed violence. It is only in the New Testament that mimetic violence fi nds its outlet in the sacrifi cial killing of Jesus Christ.